Excess Length of Acute Inpatient Stay Attributable to Acquisition of Hospital-Onset Gram-Negative Bloodstream Infection with and without Antibiotic Resistance: A Multistate Model Analysis - Hiroyuki Suzuki; Eli N Perencevich; Rajeshwari Nair; Daniel J Livorsi; Michihiko Goto (MDPI AG, 2020)
Excess length of stay (LOS) is an important outcome when assessing the burden of nosocomial infection, but it can be subject to survival bias. We aimed to estimate the change in LOS attributable to hospital-onset (HO) Escherichia coli/Klebsiella spp. bacteremia using multistate models to circumvent survival bias. We analyzed a cohort of all patients with HO E. coli/Klebsiella spp. bacteremia and matched uninfected control patients within the U.S. Veterans Health Administration System in 2003−2013. A multistate model was used to estimate the change in LOS as an effect of the intermediate state (HO-bacteremia). We stratified analyses by susceptibilities to fluoroquinolones (fluoroquinolone susceptible (FQ-S)/fluoroquinolone resistant (FQ-R)) and extended-spectrum cephalosporins (ESC susceptible (ESC-S)/ESC resistant (ESC-R)). Among the 5964 patients with HO bacteremia analyzed, 957 (16.9%) and 1638 (28.9%) patients had organisms resistant to FQ and ESC, respectively. Any HO E.coli/Klebsiella bacteremia was associated with excess LOS, and both FQ-R and ESC-R were associated with a longer LOS than susceptible strains, but the additional burdens attributable to resistance were small compared to HO bacteremia itself (FQ-S: 12.13 days vs. FQ-R: 12.94 days, difference: 0.81 days (95% CI: 0.56−1.05), p < 0.001 and ESC-S: 11.57 days vs. ESC-R: 16.56 days, difference: 4.99 days (95% CI: 4.75−5.24), p < 0.001). Accurate measurements of excess attributable LOS associated with resistance can help support the business case for infection control interventions.